(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This study provides a methodological reflection of the theoretical problems of the digital economy, it reveals the innovative characteristics of a new form of economics activity, giving rise to a new type of creative economic thinking. The author introduces a constructive neologism - “digital-economic revolution”, considers the difference between digital-economic revolution and other types of revolution. The result of the is to clarify the content and direction of the cognitive explication of the digital economy in terms of the theoretical and methodological validity. This allows to have a more correct idea of the trends of modern forms of economic activity